Effect of Fungicidal Methanol Extract of Kirinyuh Leaves (Eupatorium odoratum L.) and Noni Leaves (Morinda citrifolia L.) against MOLD Fusarium oxysporum on Tomatoes - Walidatul 'Ulya; Evie Nur Sofhiya; Etika Dyah Puspitasari (Universitas Islam Negeri Ar-Raniry, 2024)
Tomato plants are one of the leading horticultural commodities that are easily attacked by disease. Plant wilt disease is one of the diseases that often attacks tomato plants which is caused by Fusarium oxysporum. The use of chemical fungicides causes many losses, so there is a need for plant-based fungicides made from natural ingredients. Kirinyuh leaves and Noni leaves are natural ingredients that can be used as a vegetable fungicide to control fungi Fusarium oxysporum. The experiment was carried out alive and prepared using a Completely Randomized Design with 6 treatments and 6 replications. Data obtained from observations will be analyzed using the Duncan test at the 5% level. The concentrations used by each extract were 20%, 40%, 60%, and 80%, negative control (Aquadest), positive control (dithane M-45). The results showed that the Noni leaf extract fungicide with a concentration of 60% had the most effective effect in inhibiting the fungal growth zone Fusarium oxysporum on tomatoes.